Production of molecular hydrogen by mesophilic anaerobic microbial associations during the destruction of food waste - Кальсіна, С. Д. (Problems of Environmental Biotechnology, 2019)
Three mesophilic hydrogen-synthesizing anaerobic associations of microorganisms were isolated from different ecosystems. It was revealed that, by phenotypic characters, the isolated bacteria can be attributed to the genera of Bacillus sp. and Clostridium sp. Their optimal cultivation conditions under which the greatest amount of hydrogen is synthesized were investigated. It was revealed that the destruction coefficient by the water-forming anaerobic associations of microorganisms of vegetable waste is 2 times more than fruit waste.